Memahami Manusia sebagai Imago Dei Dalam Kitab Kejadian 1:26-28 - Bimba Valid Fathony Bimba Fathony (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
Humans were created in the image of God. We cannot draw literal/physical meanings, but figurative meanings. We cannot understand it like humans have hands, then God also has hands, just like human hands, the human body is the same as God's body. Humans are created in the image of God or in other words imago dei is a perfection of God in the creation of his creatures. The discussion related to understanding Man as the Imago Dei in the Book of Genesis 1: 28 will be explained by the researcher in this article. The formulation of the problem in this article includes the purpose of human creation. The nature of human nature in the Bible and how does the Book of Genesis 1: 26-28 explain human beings as Imago Dei?. Short conclusion on this article. God in creating humans positioned humans as perfect creatures. Humans as imago dei do not have a physical meaning but the meaning of expression as a form of human glory. Humans have a responsibility to carry out divine missions to manage the universe. In this study, the researcher used a qualitative approach, in which this research approach produced descriptive data in the form of written or spoken words from people and observable behavior. This research includes the type of library research.